The influence of both individual and area based socioeconomic status on temporal trends in Caesarean sections in Scotland 1980-2000 - Dundas Ruth; Fairley Lesley; Leyland Alastair H (BMC, 2011)
Abstract Background Caesarean section rates have risen over the last 20 years. Elective Caesarean section rates have been shown to be linked to area deprivation in England, women in the most deprived areas were less likely to have an elective section than those in the most affluent areas. We examine whether individual social class, area deprivation or both are related to Caesarean sections in Scotland and investigate changes over time. Methods Routine maternity discharge data from live singleton births in Scottish hospitals from three time periods were used; 1980-81 (n = 133,555), 1990-91 (n = 128,933) and 1999-2000 (n = 102,285). Multilevel logistic regression, with 3 levels (births, postcode sector and Health Board) was used to analyse emergency and elective Caesareans separately; analysis was further stratified by previous Caesarean section. The relative index of inequality (RII) was used to assess socioeconomic inequalities. Results Between 1980-81 and 1999-2000 the emergency section rate increased from 6.3% to 11.9% and the elective rate from 3.6% to 5.5%. In 1980-81 and 1990-91 emergency Caesareans were more likely among women at the bottom of the social class hierarchy compared to those at the top (RII = 1.14, 95%CI 1.00-1.25 and RII = 1.13, 1.03-1.23 respectively) and also among women in the most deprived areas compared to those in the most affluent (RII = 1.18, 1.05-1.32 and RII = 1.13, 1.02-1.26 respectively). In 1999-2000 the odds of an elective section were lower for women at the bottom of the social class hierarchy than those at the top (RII = 0.87, 0.76-1.00) and also lower in women in the most deprived areas compared to those in the most affluent (RII = 0.85, 0.73-0.99). Conclusions Both individual social class and area deprivation are independently associated with Caesarean sections in Scotland. The tendency for disadvantaged women to be more likely to receive emergency sections disappeared at the same time as the likelihood of advantaged groups receiving elective sections increased.